Electron paramagnetic resonance (EPR) study of DOPA–melanin complexes with kanamycin and copper(II) ions. Issue 3 (2011) - Najder-Kozdrowska Najder-Kozdrowska, Lidia Lidia; Pilawa Pilawa, Barbara Barbara; Buszman Buszman, Ewa Ewa; Wrześniok Wrześniok, Dorota Dorota; Więckowski Więckowski, Andrzej B. Andrzej B.
Abstract : This work comprises the study of DOPA–melanin complexes with kanamycin and copper(II) ions made by electron paramagnetic resonance EPR spectroscopy. The high concentration of paramagnetic centers in melanin makes the use of EPR spectroscopy possible. The unpaired electron localized on the oxygen atom in indol-5, 6-quinone groups is the paramagnetic centers in this polymer. The aim of this work was the analysis of EPR parameters of recorded spectra. For researches were prepared melanin complexes which differed in complexing order of drug and Cu(II) ions, and in concentration of CuCl2 solutions used during synthesis. The introduction of drugs and metal ions into melanin causes changes in EPR parameters of recorded spectra. Kanamycin causes the increase and copper(II) ions the decrease of concentrations of paramagnetic centres in melanin. Shape of EPR signal of DOPA–melanin was analyzed by fitting method. Results indicate that EPR line of DOPA–melanin is superposition of Gaussian and Lorentzian function.